APALANCAMIENTO EN MOMENTOS DE CRISIS LEVERAGE IN TIMES OF CRISIS - Llanes, Miguel DÃaz (European Scientific Journal, ESJ, 2015)
Financial leverage is a formula that companies have traditionally used to grow. At a time of expansion and growth is manifested as an interesting and inexpensive tool for business expansion. But in times of crisis, as we are from a few years ago, it is not feasible to support the growth o companies en the leverage, simply because the loans have been reduced significantly, often not renewed, and any case to higher interest rates, impossible to be paid to the profitability of companies. The measures of profitability and ROE are meaningless and must be replaced by the ROA. In times of the crisis, companies be based its growth in its assets, in its profitability over assets (ROA) and on the self-financing. And within it must emphasize on three factors forgotten and unused today: Investment in Tangible and Intangible Assets, Personal and expansion based on RDI own. Competition and growth in times of crisis will based on quality, and never on low prices.